One-year survival factors of patients with end-stage kidney disease in Bali, Indonesia - Pratiwi, Made Sindy Astri; Dewi, Ni Nyoman Gita Kharisma; Agustini, Made Priska Arya; Dewi, Putu Itta Sandi Lesmana; Fahira, Cindy; Sunaka, I Wayan (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: End-stage kidney disease (ESKD) is a global health challenge contributing to 2.2–7 million deaths annually due to inadequate treatment access. Identifying determinants of survival is critical for improving patient outcomes. To date, no study in Bali has evaluated the one-year survival of ESKD patients. Purpose: This study aimed to identify factors associated with one-year survival among patients with ESKD in Bali, Indonesia. Methods: A retrospective cohort study was conducted at Wangaya Regional General Hospital from November 2024 to March 2025, involving 210 patients aged ≥18 years diagnosed with ESKD between 2022 and 2024. Survival status was assessed over one year. Predictive factors, including age, gender, diabetes mellitus, control compliance, dialysis status, haemoglobin, blood urea nitrogen (BUN), serum creatinine (SC), and estimated glomerular filtration rate (eGFR), were analysed using Kaplan-Meier and Cox proportional hazards regression. Results: Within one year, 24.3% of ESKD patients died. The mean survival time was 9.74 months (95% CI: 9.15–10.33). Multivariate analysis identified age ≥55 years (p=0.043), non-compliance with nephrology follow-up (p<0.001), haemoglobin ≤8 g/dL (p=0.023), and BUN ≥183.5 mg/dL (p<0.001) as independent predictors of mortality. Conclusions: Older age, poor compliance, anemia, and elevated BUN were significant predictors of one-year mortality in ESKD patients. Early identification and management of these factors are essential to reduce mortality and improve patient care.